2011
DOI: 10.1007/s11010-011-0806-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pluripotent stem cells transplantation therapy for ischemic stroke

Abstract: Stroke can cause permanent neurological damage, complications, and even death. However, there is no treatment exists to restore its lost function. Human embryonic stems transplantation therapy was a novel and potential therapeutic approach for stroke. However, as we have seen, the ethical controversy pertains to embryonic stem cell research. Human induced pluripotent stem cells (iPSCs) are the latest generation of stem cells that may be a solution to the controversy of using embryonic cells. In our study, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 28 publications
2
63
0
3
Order By: Relevance
“…The studies with human iPSCs in stroke published so far provided no evidence for the formation of neuroblasts or morphologically mature neurons [25,26]. We found that at 4 months after human iPSC-derived lt-NES cells had been implanted into the striatum or cerebral cortex of Tcell-deficient rats in two different models of stroke, 73% and 77%, respectively, of grafted cells expressed the mature neuronal marker NeuN.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The studies with human iPSCs in stroke published so far provided no evidence for the formation of neuroblasts or morphologically mature neurons [25,26]. We found that at 4 months after human iPSC-derived lt-NES cells had been implanted into the striatum or cerebral cortex of Tcell-deficient rats in two different models of stroke, 73% and 77%, respectively, of grafted cells expressed the mature neuronal marker NeuN.…”
Section: Discussionmentioning
confidence: 62%
“…In support of this interpretation, the enhancement of behavioral recovery in our experiment was observed irrespective of whether the grafts were surviving at 10 weeks or not. Similarly, human iPSCs improved performance in the cylinder test from 4 days after intrastriatal implantation into stroke-damaged rats [25].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the context of ischemic stroke, an interesting study describes the use of iPS-derived neurons and astrocytes directly injected in the damaged cortex of a stroke animal model , which resulted in a reduced ischemic size with functional improvements. Another study describes the in situ migration and differentiation of human iPS cells in a similar context, with an improved sensorimotor function of the animals 4-16 days after grafting (Jiang et al 2011). …”
Section: Adult Derived Pluripotent Stem Cell Therapymentioning
confidence: 99%
“…Replacement of damaged tissue with cell-grafts or pluripotent stem cells that could differentiate into neural and glial cell populations has been widely studied (Modo et al, 2002; Jiang et al, 2011). In light of the practical and ethical issues restraining the field of stem cell research, alternative modes of stimulating neurogenesis are highly sought after.…”
mentioning
confidence: 99%